Explaining the variety of social policy responses to economic crisis how parties and welfare state structures interact - Starke, Peter 1977-; Kaasch, Alexandra 1977-; Hooren, Franca van (TranState working papers, 2011)
This paper maps and explains the reactions of four welfare states - Australia, Belgium, the Netherlands and Sweden - to three global crisis situations - the oil shocks of the 1970s, the worldwide recession of the early 1990s, and the financial crisis from 2008 onwards. Two main conclusions follow from the analysis: First, using a comprehensive typology of social policy reactions to crises, we show that crisis reactions were surprisingly diverse. There is no uniform policy response, as policies range from retrenchment through non-response to welfare state expansion. Second, explaining the variation regarding expansion vs. retrenchment we focus on the partisan composition of government, and the size of the existing welfare state, which may operate as an important automatic stabilizer during recessions. While none of these factors alone is sufficient, their interaction is able to explain most of the specific social policy responses adopted in the four countries studied.